Hello! :)
[tex]\large\boxed{\text{ Option 2.}}[/tex]
Recall the Pythagorean identity:
tan² x + 1 = sec² x
We are given:
(1 - sec x)(1 + sec x) = tan² x
Multiply using a difference of squares:
1 - sec² x = tan² x
Looking at the equation, we can see that it is not equal to the Pythagorean identity.
We can rearrange the original identity to find what (1 - sec² x) is equivalent to:
tan² x + 1 = sec² x
Move sec² x to the left hand side:
tan² x + 1 - sec² x = 0
Move tan² x to the right hand side:
1 - sec² x = -tan² x
Therefore, the identity is FALSE because (1 - sec x)(1 + sec x) = -tan² x.